1997
DOI: 10.5694/j.1326-5377.1997.tb138694.x
|View full text |Cite
|
Sign up to set email alerts
|

The GP—hospital interface: attitudes of general practitioners to tertiary teaching hospitals

Abstract: ObjectiveTo assess general practitioner (GP) perceptions of liaison with two local tertiary teaching hospitals. DesignQuestionnaire‐based survey of GP attitudes. SettingMelbourne and North West Melbourne Divisions of General Practice, in July and September 1994. ParticipantsAll GPs (587) practising in the Divisions (identified from Health Insurance Commission lists of consultations charged at GP rates). Outcome MeasuresDegree of agreement on a 5‐point Likert scale to statements about GP—hospital liaison, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 4 publications
2
20
0
Order By: Relevance
“…[21][22][23][24][25] Furthermore, shorter periods of hospitalization, coupled with increasing warfarin usage, are placing additional stresses on the community-based services caring for anticoagulated patients' post-discharge. [26][27][28] Waiting times between acute in-hospital treatment and admission to rehabilitation clinics, as well as abstention from stationary rehabilitation programs, form objective adherence barriers. [29] To overcome and to manage experiences with anticoagulation complications, many of the studies have reported the role of out-patient anticoagulation clinics, such as improving outcomes through patient engagement, improved health literacy and improved medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] Furthermore, shorter periods of hospitalization, coupled with increasing warfarin usage, are placing additional stresses on the community-based services caring for anticoagulated patients' post-discharge. [26][27][28] Waiting times between acute in-hospital treatment and admission to rehabilitation clinics, as well as abstention from stationary rehabilitation programs, form objective adherence barriers. [29] To overcome and to manage experiences with anticoagulation complications, many of the studies have reported the role of out-patient anticoagulation clinics, such as improving outcomes through patient engagement, improved health literacy and improved medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Although hospitals often utilize additional discharge paperwork, these other documents are institution-specific, not required, and not always present [27, 32-35]. Direct verbal communication between care settings is rare [27].…”
Section: Introductionmentioning
confidence: 99%
“…Historically the discharge summary has been found to be poorly written, 1,2 contain inaccurate 3–5 or ineffective 6 information, and received too late 7,8 to be of any significant value. A number of areas, identified by previous studies, have been found lacking when looking at the quality of the discharge summary.…”
Section: Introductionmentioning
confidence: 99%